A numerical study of strong-post double-faced W-beam and Thrie-beam guardrails under impacts of vehicles of multiple size classes. (September 2021) - Li, Zheng; Fang, Howie; Fatoki, Joshua; Gutowski, Matthew; Wang, Qian
Highlights: Developed FE models of double-faced W-beam and Thrie-beam guardrails. Performed nonlinear FE simulations of guardrails impacted by four different types of vehicles. Evaluated performance of double-faced W-beam and Thrie-beam guardrails at differentheights. Abstract: Median barrier systems are safety features between opposite travel lanes to redirect or prevent errant vehicles from intruding into oncoming traffic lanes. Different barriers systems have been developed and used for decades. In this study, finite element (FE) modeling and simulations were adopted to study the performance of double-faced W-beam and Thrie-beam guardrails at 29- and 31-inch installation heights. The in-service guardrail performance was evaluated under impacts of multiple sized vehicles at Test Level 4 and Test Level 5 conditions specified in Manual for Assessing Safety Hardware (MASH). The effectiveness of the guardrails was assessed using guardrail dynamic deflections, vehicle responses, and vehicle redirection characteristics. The MASH exit box criterion, MASH evaluation criterion F (roll and pitch angle limit), and MASH evaluation criterion N (vehicle trajectory) were adopted in the evaluations. Additionally, occupant safety and injury risk were determined using occupant impact velocities (OIVs), occupant ridedown accelerations (ORAs), and acceleration severity indices (ASIs). The crash simulation results showed that both W-beam and Thrie-beam guardrails could retain all test vehicles and prevent them from getting into oncoming travel lanes. All the guardrails were considered generally effective in terms of occupant risk factors and vehicle impact responses. It was also observed that in certain cases, the installation height and the type of guardrail blockout could affect the impact severity for small-sized vehicles.